Effect of Platelet Antibodies on the Ultrastructure of Normal Platelets and the Separation of Platelets Antibody Activity by Ultracentrifugation, Including one Case of Diuril Induced Thrombocytopenia Followed by Thrombocytopathy - Balboa, R. S; Gajewski, M; Pawlowski, J. M; Greenwalt, T. J; Johnson, S. A (Thrombosis and Haemostasis, 1963)
Studies on three patients with platelet antibodies associated with thrombocytopenia but with different clinical backgrounds are presented. The first patient had chronic lymphocytic leukemia without known contact with an outside source of platelet antigen. Platelet antibodies were detected before a platelet transfusion was given as a measure of platelet survival. The second patient developed a drug (Diuril) induced thrombocytopathy and thrombocytopenia. The platelets appearing in the circulation immediately following the thrombocytopenia exhibited abnormal qualitative and quantitative ultrastructure and abnormal function of platelet factor 3. This constituents the first drug induced thrombocytopathy observed. The third patient had post-hepatitic cirrhosis with functional and histologic impairment. Possible explanations of antibody production were suggested.The antibodies were demonstrated by the platelet agglutination method of Tullis using normal stored and normal stored irradiated platelets as the source of antigens. Coagulation factors were studied together with the platelet antibodies. Qualitative (platelet thromboplastic function) and quantitative (thrombocytopenia) changes were observed in one patient.Patient’s circulating platelets and agglutinated normal stored and normal stored irradiated platelets were studied under the electron microscope. Morphological changes were observed and described.The sera of the patients and normal controls were centrifuged at 126,000 g for 6 hours and platelet agglutination tests were performed with the top and bottom layers. Increased agglutination in the top layers and decreased agglutination in the bottom layers occurred in the patient’s sera without any changes in the normal sera.